An Analytical Study of the Quranic Tafsir Translation in the "Al-Quran Terjemahan Tafsir" Application - Jannah, Uzlifatil; Sulthoni, Akhmad; Ridho, Mukharrom (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2024)
Quranic tafsir plays a crucial role in facilitating the understanding of the Quran. Initially, interpretations were conducted in Arabic, but as Islam spread worldwide, these interpretations were translated into various languages. With technological advancements, many tafsirs are now available online, such as on websites and mobile applications. This research examines the source references, strengths, and weaknesses of the tafsir translations in the "Al-Quran Terjemahan Tafsir", one of the available Quranic tafsir applications in Indonesia. This study employs a literature review with a descriptive-analytical method by collecting, processing, and analyzing online data from the application. The results of the study indicate that, first, the translation of Tafsir Ibn Kathir in the "Al-Quran Terjemahan Tafsir" application refers to the translated book of Tafsir Ibn Kathir published by PT. Sinar Baru Algensindo, available in ebook format from kampungsunnah.org. Secondly, the strength of this application lies in the completeness of its source references, which are not abridged. However, it lacks a clear citation of source references and has flaws in its layout and writing, which may cause confusion for readers in understanding the content presented.